Nitridation and Layered Assembly of Hollow TiO2 Shells for Electrochemical Energy Storage. (19th September 2013) - Moon, Geon Dae; Joo, Ji Bong; Dahl, Michael; Jung, Heejung; Yin, Yadong
<x xml:space="preserve">Abstract</x> The nitridation of hollow TiO2 nanoshells and their layered assembly into electrodes for electrochemical energy storage are reported. The nitridated hollow shells are prepared by annealing TiO2 shells, produced initially using a sol–gel process, under an NH3 environment at different temperatures ranging from 700 to 900 °C, then assembled to form a robust monolayer film on a water surface through a quick and simple assembly process without any surface modification to the samples. This approach facilitates supercapacitor cell design by simplifying the electrochemical electrode structure by removing the need to use any organic binder or carbon‐based conducting materials. The areal capacitance of the as‐prepared electrode is observed to be ≈180 times greater than that of a bare TiO2 electrode, mainly due to the enhanced electrical conductivity of the TiN phase produced through the nitridation process. Furthermore, the electrochemical capacitance can be enhanced linearly by constructing an electrode with multilayered shell films through a repeated transfer process (0.8 to 7.1 mF cm–2, from one monolayer to 9 layers). Additionally, the high electrical conductivity of the shell film makes it an excellent scaffold for supporting other psuedocapacitive materials (e.g., MnO2), producing composite electrodes with a specific capacitance of 743.9 F g–1 at a scan rate of 10 mV s–1 (based on the mass of MnO2) and a good cyclic stability up to 1000 cycles.